الدور التنموي الاقتصادي - الاجتماعي للأنشطة الاستثمارية في المناطق الحرة السورية - عثمان, سلمان; شحرور, سميع (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يعالج البحث موضوعا حيويا يتعلق بالدور التنموي للأنشطة الاستثمارية القائمة في المناطق الحرة السورية. فالمناطق الحرة تعد أهم الوسائل الاقتصادية التي تلجأ لها الدول لتحقيق أهداف التنمية وخاصة في جذب الاستثمارات الأجنبية والمحلية والزيادة في حركة التبادل التجاري. كما تلعب المناطق الحرة دورا تنمويا واجتماعيا ايجابيا من خلال استقطاب وتشغيل الأيدي العاملة الوطنية الرخيصة بمستوياتها المختلفة من خلال توفير فرص العمل. ومن خلال دراسة تحليلية مقارنة باستقراء نشوء وتطور المناطق الحرة وأهميتها بالإضافة إلى أهمية الاستثمار في المناطق الحرة السورية ومقومات نجاحه والأنشطة الاستثمارية القائمة من جهة, والدور التنموي للأنشطة الاستثمارية في المناطق الحرة السورية من الجهة الأخرى, ليتوصل البحث إلى جملة من النتائج وأهمها: - يعد المناخ الاستثماري في المناطق الحرة السورية محفزاً للاستثمار الاجنبي والمحلي.- هناك نمو واضح في حركة التبادل التجاري.- هناك دور ضعيف للمناطق الحرة السورية في الحد من نسبة البطالة في المجتمع.The research handles a vital topic regarding the developmental role of investment activities in the free zones. The free zones are the most important economic instruments employed by countries to achieve the development goals, especially. In Attracting foreign and domestic investments and the increase in traffic trade. Besides, the free zones play a developmentally and socially positive through polarization and running cheap national labor in it's different levels through job creation.Through comparative analysis approach and reviewing the historical growth, development of free zones and their importance in addition to the importance of investment in Syrian free zones and its success and investment activities on the one hand, and the developmental role of investment activities in the Syrian free zones, on the other hand, this study seeks set of results which the most important of it:- The investment climate in Syrian free zones as a catalyst for foreign and domestic investment.- There is a clear growth in traffic trade.- There is a weak role of Syrian free zones in reducing unemployment in the community.